Diversity‐Oriented Synthesis of Furo[3, 2‐c]coumarins and Benzofuranyl Chromenones through Chemoselective Acylation/Wittig Reaction. Issue 6 (5th January 2018) - Yang, Shu‐Mei; Wang, Chein‐Yi; Lin, Chun‐Kai; Karanam, Praneeth; Reddy, Ganapuram Madhusudhan; Tsai, Yi‐Ling; Lin, Wenwei
Abstract: A highly efficient and chemoselective one‐pot protocol for the diversity‐oriented synthesis of two types of coumarin‐based formal cross‐coupling adducts, furo[3, 2‐c]coumarins and 3‐benzofuranyl chromenones, is described. Key attributes of the methodology are an initial chemoselective acylation of functionalized phosphorus zwitterions and a subsequent chemoselective intramolecular Wittig reaction that preferentially resulted in one of the two coumarin derivatives in high yield, depending on relative reactivities and the addition sequence of the acylating agents. Abstract : Double agents without the mystery : In the efficient diversity‐oriented synthesis of two types of coumarin‐derived polyheterocycles, furo[3, 2‐ c ]coumarins and 3‐benzofuranyl chromenones, the chemoselective acylation of phosphorus zwitterions was followed by a chemoselective intramolecular Wittig reaction (see scheme). The judicious choice of acylating agents and their addition sequence created a difference in reactivity in the Wittig reaction.